(untitled) (Journal of the Sociology and Theory of Religion, 2020)
The regional costume is a highly cultural reference in Segovia (Spain). Dressing up as ’mayor’ entails holding unlawfully a position, a public dignity act that still prevails even when the de-facto power is exercised by both genders. A ritual of dressing up, a celebration and an attire which originated in the autochthonous narrative of territorial constitution, providing a greater meaning to this religious communal rite, but because of its complexity, it possesses traits which surpass the winter rituals of inversion, therefore it can be considered as the Total Rite. In this paper it is analyzed the costume, its history, elements and signifiers under a documentary, In-depth interviews and participatory observation.